Representations of black queer identities in South African film and visual culture: Transgressive vulnerability as a mechanism for imagining and claiming space, visibility and freedom. - Majikijela, Lwando (My University, 2022)
In South Africa, there have been widespread debates on space and visibility of gender and sexual minorities amongst scholars from different fields, including queer, feminist, anti-racist and cultural theorists. A great deal of this scholarly interest stems from how gender and sexual minorities have been subjected to forms of discrimination, homophobia and violence despite the promises of the Constitution of South Africa (1996) to protect queer rights. In the post-apartheid period, queer people still find it challenging to live visible and freer lives in the spaces they move in. Livermon (2012: 300) claims that the lives of “black queer people in specifically black cultural spaces continue to be policed”, which suggests that South Africans broadly have not included queer people in the idyllic construct of the rainbow nation. This state of affairs raises questions of how queer subjects are understood and understand themselves in South African spaces, and how they are disconnected from spaces that uphold heteronormative values. In addition, it highlights the limits on queer visibly and restrictions on queer performativity, when these performativities and visibilities are met with discrimination, oppression and violence. Film and visual culture have been important platforms to push back against these restrictive social and cultural structures. In this project, I explore four films, namely Simon & I (2002), While You Weren’t Looking (2015), Out of This World (2018) and Inxeba (The Wound) (2017), and discuss how black queer subjects are represented in films and visual culture particularly in relation to spaces they move in. Queer people are often framed as vulnerable in public discourse. Butler (2014) claims that vulnerabilities can be thought about as the birthplace of resistance; this is what Butler et al. (2016) refer to as vulnerability as a condition that can lead to objective ontological claims for acquiring visibility, freedom and space for liveable lives. This project will explore two main topics, namely (i) how space, visibility and freedom are represented in queer visual narratives and other associated texts in post-apartheid South Africa, and (ii) rethinking forms of vulnerabilities as agential and as opening space for resistance in these visual media and visual performativities. The project will analyse how black queer subjects are represented in film and mainstream media in order to demonstrate the important interventions made by the visual texts explored in this thesis. The project uses queer theory, including the work of Bulter (2014), Macharia (2009, 2019) and Ahmed (2006) to understand forms of visual performativity as related to vulnerability. The project uses qualitative visual content analysis 4 to unpack the complex social and cultural dynamics represented in these texts, and the analysis demonstrates how these visual texts are themselves sites of resistance and of imagining and claiming “liveable lives” (Butler, 2014) that the transgressive vulnerabilities allow for.
A research report submitted in partial fulfilment of the requirement for the Degree of Master of Arts in Media Studies to the Faculty of Humanities, University of the Witwatersrand, 2021